Financial cost of assisted reproductive technology for patients in high-income countries: A systematic review protocol - Purity Njagi; Wim Groot; Jelena Arsenijevic; Gitau Mburu; Georgina Chambers; Carlos Calhaz-Jorge; James Kiarie (PLoS ONE, 2025)
Background Infertility affects one in six people globally, with similar prevalence rates across high-income and low- and middle-income countries. Technological advancements, particularly in Assisted Reproductive Technology (ART), have improved fertility treatment options. Although access to ART is presumed to be better in high-income countries (HICs), economic factors and eligibility restrictions could still impact effective utilization in these settings. Informed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocols (PRISMA-P), this protocol outlines the methodological and analytical approaches to examine the ART costs paid by patients in HICs and the correlation with economic indicators and ART regulatory frameworks. Methods Following the PRISMA approach, we will search for articles indexed in PubMed, EMBASE, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Web of Science, PsycINFO, and Latin American & Caribbean Health Sciences Literature (LILACS). Grey literature from relevant organizations’ virtual databases will also be searched. The review will encompass studies published between 2001 and 2024, with the primary outcome being ART direct medical and direct non-medical costs, while secondary outcomes shall include ART financing arrangements. The review will synthesize ART costs, adjusting them to USD Purchasing Power Parity for cross-country comparison, and correlate findings with GNI per capita and ART financing policies. The Integrated Quality Criteria for Review of Multiple Study Designs (ICROMS) tool will be utilized to evaluate the quality of the included studies. We will conduct a meta-analysis if the studies provide sufficient cost-effect size estimates. Discussion The review findings will contribute to our understanding of the potential financial burden faced by (disadvantaged) individuals in HICs due to ART costs. Additionally, the review shall highlight the implications that ART financing policies have in enhancing access and affordability, offering valuable insights for healthcare planning and policy formulation. The results will be disseminated through a peer-reviewed journal article and relevant international conferences. Trial registration Systematic review registration: PROSPERO number: CRD42023487655.